Challenges in diagnosis and treatment of long COVID - Gu, Lei; Yue, Jian; Lin, Jing; Liu, Zeyi; Huang, Jian-an (Frontiers in Medicine, 2025)
Despite a large population affected by COVID-19, awareness of long COVID among clinicians is surprisingly limited. This has led to delayed or missed diagnoses and, consequently, inappropriate treatments that fail to address patients’ specific needs. Our study highlights the gaps in knowledge and the barriers to effective management of long COVID in the healthcare system. Through this work, we aim to bring attention to these critical issues and advocate for urgent action to improve the clinical management of long COVID.